SARS-CoV-2 delta (B.1.617.2) spike protein adjuvanted with Alum-3M-052 enhances antibody production and neutralization ability - Huang, Hong; Zhou, Zhongcheng; Xiong, Xinxin; Liu, Zhihai; Zheng, Xiaoxue; Quan, Qingli; Yu, Meixing (Frontiers in Public Health, 2023)
Optimizing adjuvant is one of the critical methods to improve the vaccine. 3M-052, a novel TLR7/8 agonist which was designed for slow dissemination at the injection site, has a potential as adjuvant, but its performance as a vaccine adjuvant for SARS-CoV-2 spike protein has not been studied. Here we found sera of mice immunized by SARS-CoV-2 (B.1.617.2) spike protein adjuvanted with Alum-3M-052 had higher antibody titers and higher neutralization efficiency against both SARS-CoV-2 (BA.2.12.1) pseudovirus and SARS-CoV-2 (B.1.617.2) pseudovirus, compared with that of mice immunized with spike protein adjuvanted with Alum. Besides, we also found neutralization efficiency of anti-SARS-CoV-2 (B.1.617.2) spike protein antibody against SARS-CoV-2 (BA.2.12.1) pseudovirus was lower than that of SARS-CoV-2 (B.1.617.2) pseudovirus. This study provided evidence for the application of Alum-3M-052 as an adjuvant in COVID-19 vaccines production.